(untitled) (Ustozlar uchun, 2025)
In recent years, creativity has become one of the most essential skills in modern education. Developing creativity from an early age helps children express themselves, solve problems, and think independently. Creative tasks in the classroom promote imagination, curiosity, and emotional development. In preschool and primary education, teachers play a crucial role in fostering creativity through purposeful and engaging activities.